2016
DOI: 10.1016/j.jvs.2016.01.048
|View full text |Cite
|
Sign up to set email alerts
|

The perioperative effect of concomitant procedures during open infrarenal abdominal aortic aneurysm repair

Abstract: Introduction Open repair of abdominal aortic aneurysms (AAA) is occasionally performed in conjunction with additional procedures. However, it is unclear how these concomitant procedures affect outcome. This study aims to determine the frequency of additional procedures during elective open AAA repair and the impact on perioperative outcomes. Methods Between January 2003 and November 2014, all elective infrarenal open AAA repairs in the Vascular Study Group of New England (VSGNE) were identified. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Some studies indicated that performing adjunctive RR during open AAA repair was associated with an increased risk of operative morbidity and mortality. 12) In contrast, others reported the feasibility of simultaneous renal and aortic reconstruction because they found similar outcomes to IR aortic repair. 13) …”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that performing adjunctive RR during open AAA repair was associated with an increased risk of operative morbidity and mortality. 12) In contrast, others reported the feasibility of simultaneous renal and aortic reconstruction because they found similar outcomes to IR aortic repair. 13) …”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies have shown increased morbidity and mortality related to concomitant procedures with open or endovascular repair of abdominal aorta 22,23. However, in patients with advanced atherosclerotic disease, it is sometimes necessary to perform additional procedures, for example, thromboendarterectomy of the groin arteries or even infrainguinal bypass, to ensure postoperative graft patency.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies have shown increased morbidity and mortality related to concomitant procedures with open or endovascular repair of abdominal aorta. 22 , 23 However, in patients with advanced atherosclerotic disease, it is sometimes necessary to perform additional procedures, for example, thromboendarterectomy of the groin arteries or even infrainguinal bypass, to ensure postoperative graft patency. We have previously, in a comparative cohort study design in the same patient population, found a significant relative reduction of the composite events (all-cause mortality, graft occlusion and systemic morbidity) in patients with LABFB as compared to open ABFB, during a median follow-up time period of 4.12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal aortic aneurysm (AAA) infrequently co-exists with visceral/renal artery pathologies needing concomitant treatment, where a higher technical complexity and a higher risk for morbidity/mortality are anticipated [ 1 , 2 ]. A 77-year-old male patient underwent computed tomography for weight loss and postprandial pain presenting a 65-mm infrarenal AAA, 35-mm right common iliac aneurysm, left internal iliac artery occlusion, 35-mm right renal artery aneurysm (RAA), occluded superior mesenteric artery (SMA), occluded left renal artery and median arcuate ligament syndrome ( Fig.…”
mentioning
confidence: 99%